2016
DOI: 10.1021/acsami.6b00388
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Fe3O4/GCs Composites and Their Enhanced Microwave Absorption Properties

Abstract: Graphene has good stability and adjustable dielectric properties along with tunable morphologies, and hence can be used to design novel and high-performance functional materials. Here, we have reported a facile synthesis method of nanoscale Fe3O4/graphene capsules (GCs) composites using the combination of catalytic chemical vapor deposition (CCVD) and hydrothermal process. The resulting composite has the advantage of unique morphology that offers better synergism among the Fe3O4 particles as well as particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
231
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(241 citation statements)
references
References 41 publications
10
231
0
Order By: Relevance
“…Among these hybrids, heteronanostructured hybrids have been proved to exhibit strong EM wave absorption properties because of their interfacial and synergistic effects. Therefore, different categories of heteronanostructured hybrids were developed to further improve their EM wave absorbing capabilities, such as Fe@ZnO11, Fe 3 O 4 @SiO 2 12, Fe 3 O 4 @SnO 2 13, FeCo@ZnO14, Ni@TiO 2 15, and so on16171819. Generally, the previously reported results indicated that the microwave absorption (MA) capability of MAMs was mainly determined by the ε r , μ r , EM impedance matching and microstructure.…”
mentioning
confidence: 99%
“…Among these hybrids, heteronanostructured hybrids have been proved to exhibit strong EM wave absorption properties because of their interfacial and synergistic effects. Therefore, different categories of heteronanostructured hybrids were developed to further improve their EM wave absorbing capabilities, such as Fe@ZnO11, Fe 3 O 4 @SiO 2 12, Fe 3 O 4 @SnO 2 13, FeCo@ZnO14, Ni@TiO 2 15, and so on16171819. Generally, the previously reported results indicated that the microwave absorption (MA) capability of MAMs was mainly determined by the ε r , μ r , EM impedance matching and microstructure.…”
mentioning
confidence: 99%
“…According to the transmission line theory, permeability and permittivity are the most important factors in the microwave absorbing properties that have been provided by magnetic nanoparticles, dielectric silicone rubber, and dielectric MWCNTs. Moreover, because of homogenous coating of nanoparticles base on the functionalized MWCNTs through the sonochemical and solvothermal complementary methods, interfacial polarization and Maxwell-Wagner effect was reinforced that enhanced charges accumulation and microwave absorption of sample [9,13]. Magnetic loss of the spinel ferrites because of eddy current loss effect and conductive loss of the MWCNTs according to the free electron theory caused the desirable microwave absorption in this nanocomposite [9,11].…”
Section: Microwave Absorption Propertiesmentioning
confidence: 97%
“…Modified Ba 0.2 Sr 0.2 La 0.6 MnO 3 nanoparticles have absorbed 22.36 dB at 14.78 GHz and showed that can be a promissing microwave absorber between the other magnetic nanoparticles [1]. Recently, Polyaniline, polypyrrole, graphene, and carbon nanotube as the conductive polymers were used to dielecteric loss of the microwave absorbent nanocomposite [2,3,5,[9][10][11][12]. One of the most important factors having effect on the microwave attenuation is the polimeric matrix effect of the microwave absorbent samples.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration and preparation of high-performance microwave absorption materials is an effective approach to resolve the challenge related to EMI pollution. In practical application, excellent the microwave absorbing material usually has the advantages of low density, low thickness strong absorption at a broad frequency and high thermal stability [1]. At present, microwave absorbing material is one of typical functional materials and has a variety of applications in EMI shielding and countermeasure to radar detection [2,3].…”
Section: Introductionmentioning
confidence: 99%